International Recommendations for the Diagnosis and Management of Patients With Adrenoleukodystrophy: A Consensus-Based Approach. (22nd November 2022) - Engelen, Marc; van Ballegoij, Wouter J.C.; Mallack, Eric James; Van Haren, Keith P.; Köhler, Wolfgang; Salsano, Ettore; van Trotsenburg, A.S.P.; Mochel, Fanny; Sevin, Caroline; Regelmann, Molly O.; Tritos, Nicholas A.; Halper, Alyssa; et al.
Abstract : Pathogenic variants in the ABCD1 gene cause adrenoleukodystrophy (ALD), a progressive metabolic disorder characterized by 3 core clinical syndromes: a slowly progressive myeloneuropathy, a rapidly progressive inflammatory leukodystrophy (cerebral ALD), and primary adrenal insufficiency. These syndromes are not present in all individuals and are not related to genotype. Cerebral ALD and adrenal insufficiency require early detection and intervention and warrant clinical surveillance because of variable penetrance and age at onset. Newborn screening has increased the number of presymptomatic individuals under observation, but clinical surveillance protocols vary. We used a consensus-based modified Delphi approach among 28 international ALD experts to develop best-practice recommendations for diagnosis, clinical surveillance, and treatment of patients with ALD. We identified 39 discrete areas of consensus. Regular monitoring to detect the onset of adrenal failure and conversion to cerebral ALD is recommended in all male patients. Hematopoietic cell transplant (HCT) is the treatment of choice for cerebral ALD. This guideline addresses a clinical need in the ALD community worldwide as the number of overall diagnoses and presymptomatic individuals is increasing because of newborn screening and greater availability of next-generation sequencing. The poor ability to predict the disease course informs current monitoring intervals but remains subject to change as more data emerge. This knowledge gap should direct future research and illustrates once again that international collaboration among physicians, researchers, and patients is essential to improving care.